2020
DOI: 10.1186/s12870-020-02679-8
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance involved candidate genes in rice: an integrative meta-analysis approach

Abstract: Background Salinity, as one of the main abiotic stresses, critically threatens growth and fertility of main food crops including rice in the world. To get insight into the molecular mechanisms by which tolerant genotypes responds to the salinity stress, we propose an integrative meta-analysis approach to find the key genes involved in salinity tolerance. Herein, a genome-wide meta-analysis, using microarray and RNA-seq data was conducted which resulted in the identification of differentially ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…Among them, 20 genes localized in the QTL hotspot regions for yield and ion homeostasis are promising potential candidates for enhancing salt tolerance in rice and are validated for differential gene expression using qRT-PCR. Our results are in broad agreement with those of Mirdar-Mansuri et al (2020) for the families of candidate genes detected in meta-QTL. These potential candidate genes are listed in Online Resource 3 and include pectinesterase, peroxidase, oxidoreductase of the aldo/keto reductase family, inorganic phosphate transporter, transcription regulators and OsHKT1.…”
Section: Candidate Genes Associated With Salinity Tolerancesupporting
confidence: 89%
See 1 more Smart Citation
“…Among them, 20 genes localized in the QTL hotspot regions for yield and ion homeostasis are promising potential candidates for enhancing salt tolerance in rice and are validated for differential gene expression using qRT-PCR. Our results are in broad agreement with those of Mirdar-Mansuri et al (2020) for the families of candidate genes detected in meta-QTL. These potential candidate genes are listed in Online Resource 3 and include pectinesterase, peroxidase, oxidoreductase of the aldo/keto reductase family, inorganic phosphate transporter, transcription regulators and OsHKT1.…”
Section: Candidate Genes Associated With Salinity Tolerancesupporting
confidence: 89%
“…In addition, these meta-QTL regions also possess candidate genes related to a wide range of functions including stress signaling and sensing pathways, genes coding integral membrane components, cell wall organization (wall-associated kinases), serine/threonine (Ser/Thr) kinases, pectinesterases, osmotic adjustment (chitinases, hydrolases), transcription factors regulating stress specific genes, ion homeostasis (Na + and K + transporters and vacuolar Na + /H + exchangers) and other related genes. Some of the candidate genes present in these hotspot regions have been validated (Islam et al 2019;Mirdar-Mansuri et al 2020), while other needs to be validated for their tolerance in different genetic backgrounds. In addition to these QTL hotspots, there are several genomic regions with 5-10 traits associated with salinity tolerance.…”
Section: Qtl Hotspots For Introgression Of Salinity Tolerance In Ricementioning
confidence: 99%
“…The salt stress tolerance of rice is related to the genotype, and different genotypes show discrepant salt stress tolerance (Ganie et al, 2016;Mansuri et al, 2019). Hundreds of salt stress-related QTLs have been identified among different rice populations to date (Kong et al, 2019b;Mansuri et al, 2020). However, only four salt stress-related genes have been cloned and experimentally verified in rice, namely, SKC1 (Lin et al, 2004;Hauser and Horie, 2010), HST1 (Takagi et al, 2015), OsHAK21 (He et al, 2019), and OsSTLK (Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…11 salt stress-related Meta-QTLs were reported via integrating QTL information from 12 studies (Islam et al, 2019). Recently, Mansuri et al (2020) identified 46 Meta-QTLs of salt stress-related traits, including salinity tolerance score, shoot potassium concentration, shoot sodium concentration, chlorophyll content, shoot dry weight trait, etc., (Mansuri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these meta-QTL regions also possess candidate genes related to a wide range of functions including stress signaling and sensing pathways, genes coding integral membrane components, cell wall organization (Wall Associated Kinases), Serine/Threonine (Ser/Thr) kinases, pectinesterases, osmotic adjustment (chitinases, hydrolases), transcription factors regulating stress speci c genes, ion homeostasis (Na + and K + transporters and vacuolar Na + /H + exchangers) and other related genes. Some of the candidate genes present in these hotspot regions have been validated (Islam et al 2019;Mirdar Mansuri, 2020), while other needs to be validated for their tolerance in different genetic backgrounds. In addition to these QTL hotspots, there are several genomic regions with 5-10 traits associated with salinity tolerance.…”
Section: Qtl Hotspots For Introgression Of Salinity Tolerance In Ricementioning
confidence: 99%